A new instrumentation for in situ characterization of the charge transport and crystallographic properties in co-evaporated organic thin film transistor. (1st September 2016) - Watanabe, Takeshi; Kikuchi, Mamoru; Nishida, Kousaku; Koganezawa, Tomoyuki; Hirosawa, Ichiro; Yoshimoto, Noriyuki
ABSTRACT: A new instrumentation was developed to study the in situ electrical and crystallographic properties of organic thin film transistor during vacuum deposition. We characterized pentacene (PEN) and perfluoro-pentacene (PFP) co-deposited organic thin film transistor with various mixing ratio using this equipment. Lattice parameters and crystal orientations of PEN and PFP alloyed phases (named σ-phase and λ-phase) were determined using an in situ two-dimensional grazing incidence X-ray diffraction (2D-GIXD) measurement. The observed 2D-GIXD patterns clarified that the σ-phase is in triclinic unit cell with the following lattice parameters: a = 0.67 nm, b = 0.75 nm, c = 1.58 nm, α = 95.7° β = 94.2° and γ = 84.0°. The c plane of σ-phase crystal is parallel to the substrate surface. The λ-phase is also in triclinic with the following lattice parameters: a = 0.66 nm, b = 0.69 nm, c = 1.56 nm, α = 109.5° β = 113.0° and γ = 81.5°. The a plane of λ-phase crystal was parallel to the substrate surface. It was also found the best symmetric hole and electron mobility (μh = 5.5 × 10 −4 cm 2 V −1 s −1 and μe = 5.1 × 10 −4 cm 2 V −1 s −1 ) were obtained at PEN: PFP = 1:1.